Operating system concepts with Java : international students version - Silberschatz, Abraham; Gagne, Greg; Galvin, Peter Baer (John Wiley & Sons, 2011)
The award-winning team of Abraham Silberschatz, Peter Galvin, and Greg Gagne gets system administrators right up to speed on all the key concepts of computer operating systems. This new edition gives them a thorough theoretical foundation that they can apply to a wide variety of systems as they progress to the next level of their computer work